Avaliação da integridade de córregos a partir das características da paisagem: teste do protocolo WHEBIP para uma região tropical - Pires, Adriana Helena Catojo (Universidade Federal de São Carlos, 2013)
Lotic systems are highly influenced by the landscape through which they flow, and changes in the landscape are the main threat to their ecological integrity. Evaluating the ecological "health" of lotic systems is essential and of great importance to the management of water resources worldwide. In this study, we evaluated the integrity of streams in southeastern Brazil using the protocol WHEBIP (Watershed Habitat Evaluation and Biotic Integrity Protocol), which combines information about the coverage of riparian vegetation, geomorphology, land cover and human activities to assess the physical characteristics of the sub-basin and to evaluate the integrity of streams. We compared this protocol with the protocol RCE (Riparian, Channel and Environmental), already widely used in tropical regions, to directly assess stream physical condition. As a measure of the functional integrity of streams, we estimated leaf breakdown rates, an important process in lotic systems. Furthermore, we sorted and identified the macroinvertebrates that colonized leaves in the 2nd and 28th days of the decomposition experiment and calculated environmental quality metrics related to these communities to test their relationship with WHEBIP. The protocols WHEBIP and RCE were significantly correlated to each other, with greater differentiation among streams especially when RCE was high. Possibly, the WHEBIP, by incorporating spatial variables on a large scale in the landscape, best differentiates these streams. None of the protocols tested were correlated with leaf breakdown rates. However, when calculating variation of decay rates (standard error), we observed a positive relationship with the protocol WHEBIP. Thus, we grouped the metrics of the protocol WHEBIP in a Principal Component Analysis (PCA), noting the trend to a significant correlation between changes in leaf breakdown rates and the first axis of the PCA, which indicates that the increase of forest cover in the microbasin could reduce variation in leaf breakdown rates in streams. The WHEBIP and RCE showed no correlation with the environmental quality metrics related to macroinvertebrate communities. But we tested the hypothesis that higher values of WHEBIP decreases the variation in leaf breakdown rates due to higher stability of macoinvertebrate communities, we found a significant correlation to withdraw one of the streams of the analysis. This stream differed greatly from the rest, because even getting down in value in WHEBIP, showed a differentiation between communities, due to the dominance of certain taxa in the days analyzed. This is the first study in the tropics that relates the variation in leaf breakdown rates in streams and forest cover of the microbasin within they are inserted. Our results suggest that WHEBIP protocol can be used to assess the integrity of streams in tropical regions. This protocol showed significant relationships with the variation in leaf breakdown rates, which may prove to be an interesting metric for use in monitoring, and the stability of the macroinvertebrate community, which is greater in less impacted streams, as suggested by other studies.
Keywords: Ecologia; Ecossistemas aquáticos; Decomposição foliar; Macroinvertebrados aquáticos; WHEBIP; RCE; Integridade de córregos; SIG; Stream integrity; Leaf breakdown; Macroinvertebrates; CIENCIAS BIOLOGICAS::ECOLOGIA